2021
DOI: 10.1080/23273798.2021.1909084
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a foreign accent introduces lexical integration difficulties during late semantic processing

Abstract: The presence of a foreign accent introduces lexical integration difficulties during late semantic processingPrevious research suggests that native listeners may be more tolerant to syntactic errors when they are produced in a foreign accent. However, studies investigating this topic within the semantic domain remain conflicting. The current study examined the effects of mispronunciations leading to semantic abnormality in foreign-accented speech.While their EEG was recorded, native speakers of Spanish listened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 53 publications
4
10
0
Order By: Relevance
“…Recall that the speakers recorded both correct and incorrect versions of the sentences in real time. In line with similar past ERP research (Gosselin et al, 2021;Grey et al, 2019Grey et al, , 2020Xu et al, 2020;Caffarra & Martin, 2019;Grey & van Hell, 2017;Hanulíková et al, 2012), incorrect critical determiner phrases were not cross-spliced onto grammatically correct sentences to prioritize naturalistic, co-articulated speech. To ensure that the speakers had not unconsciously introduced prosodic "markers" of an upcoming error in the stimulus (e.g., differences in speech rate, pitch, pauses), each sentence was trimmed immediately before the target noun and presented to 30 additional native speakers of Spanish (M age = 23.8 years, SD = 4.7, 20 women, 10 men).…”
Section: Methodssupporting
confidence: 79%
See 3 more Smart Citations
“…Recall that the speakers recorded both correct and incorrect versions of the sentences in real time. In line with similar past ERP research (Gosselin et al, 2021;Grey et al, 2019Grey et al, , 2020Xu et al, 2020;Caffarra & Martin, 2019;Grey & van Hell, 2017;Hanulíková et al, 2012), incorrect critical determiner phrases were not cross-spliced onto grammatically correct sentences to prioritize naturalistic, co-articulated speech. To ensure that the speakers had not unconsciously introduced prosodic "markers" of an upcoming error in the stimulus (e.g., differences in speech rate, pitch, pauses), each sentence was trimmed immediately before the target noun and presented to 30 additional native speakers of Spanish (M age = 23.8 years, SD = 4.7, 20 women, 10 men).…”
Section: Methodssupporting
confidence: 79%
“…had a strong, detectable nonnative accent, but that they were as intelligible as the Spanish speakers. Though the informants were highly accurate in detecting syntactic errors overall, native-accented errors were identified at a higher rate than English-accented errors (see Gosselin et al, 2021;Grey & van Hell, 2017;Hanulíková et al, 2012, for similar results).…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Hanulikova et al (2012) observed a similar N400 effect during listening to both native and foreign-accented spoken sentences with semantic violations (cf. Gosselin et al 2021). While Goslin et al (2012) found a reduced N400 effect in correctly spoken sentences during foreign accent listening as opposed to regional or native listening.…”
Section: Introductionmentioning
confidence: 86%